discrete not continuous

Calculus Level 4

l i m n i = 1 n l o g i i ( l o g n ) 2 = ? lim_{n\rightarrow \infty}\frac{\sum_{i=1}^n \frac{log\: i}{i}}{(log\: n)^2}=?


The answer is 0.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Firstly we see that the series i = 1 ln ( i ) i \displaystyle \sum_{i=1}^{\infty} \frac{\ln(i)}{i} is divergent(By Cauchy Condensation Test ) and hence the sequence of partial sums which is S n = i = 1 n ln ( i ) i \displaystyle S_{n}=\sum_{i=1}^{n} \frac{\ln(i)}{i} must be a divergent sequence and it diverges to positive infinity.

Also the sequence ( ln ( n ) ) 2 \displaystyle (\ln(n))^{2} is monotone , divergent and tends to positive infinity.

So we can apply the Stolz-Cesaro Theorem :-

So we have to solve the following limit:- lim n S n + 1 S n ( ln ( n + 1 ) ) 2 ( ln ( n ) ) 2 = lim n ln ( n + 1 ) n + 1 ( ln ( n + 1 ) ln ( n ) ) ( ln ( n + 1 ) + ln ( n ) ) \displaystyle \lim_{n\to\infty} \frac{S_{n+1}-S_{n}}{(\ln(n+1))^{2}-(\ln(n))^{2}} =\lim_{n\to\infty} \frac{\frac{\ln(n+1)}{n+1}}{\left(\ln(n+1)-\ln(n)\right)\left(\ln(n+1)+\ln(n)\right)}

Notice that this is neither in 0 0 \displaystyle \frac{0}{0} form nor the \displaystyle \frac{\infty}{\infty} form . Hence you cannot apply L'Hopital or Stolz Cesaro again without making certain rearrangements first. Rearranging the expression a little we get:-

lim n 1 ( n + 1 ) ln ( 1 + 1 n ) ln ( n + 1 ) ln ( n ) + ln ( n + 1 ) \displaystyle \lim_{n\to\infty}\frac{1}{(n+1)\ln(1+\frac{1}{n})}\cdot \frac{\ln(n+1)}{\ln(n)+\ln(n+1)}

Now both of the sequences :- 1 ( n + 1 ) ln ( 1 + 1 n ) \displaystyle \frac{1}{(n+1)\ln(1+\frac{1}{n})} and ln ( n + 1 ) ln ( n ) + ln ( n + 1 ) \displaystyle \frac{\ln(n+1)}{\ln(n)+\ln(n+1)} are convergent and so we can evaluate the limits separately and then multiply them to get the answer.

lim n 1 ( n + 1 ) ln ( 1 + 1 n ) = lim n 1 ( n + 1 ) ( 1 n 1 2 n 2 O ( 1 n 3 ) ) = 1 \displaystyle \lim_{n\to\infty} \frac{1}{(n+1)\ln(1+\frac{1}{n})} = \lim_{n\to\infty} \frac{1}{(n+1)\left(\frac{1}{n} - \frac{1}{2n^{2}} -O(\frac{1}{n^{3}})\right)} = 1

Again for the sequence lim n ln ( n + 1 ) ln ( n ) + ln ( n + 1 ) = 1 2 \displaystyle \lim_{n\to\infty}\frac{\ln(n+1)}{\ln(n)+\ln(n+1)}= \frac{1}{2} . For the proof you can apply L'Hopital rule . But I don't think you need to. it is enough to just consider lim n ln ( n + 1 ) ln ( n ) = 1 \displaystyle \lim_{n\to\infty} \frac{\ln(n+1)}{\ln(n)} = 1 . This is achieved immediately by applying Sandwich Theorem .

Now the answer follows directly and it is 1 2 \displaystyle \frac{1}{2}

Haroun Meghaichi
Sep 5, 2014

By the integral test inequality by have : i = 1 n log i i 1 n log x x d x = log 2 n 2 \sum_{i=1}^n \frac{\log i}{i} \sim \int_1^n \frac{\log x}{x} \ \mathrm{d}x = \frac{\log^2 n}{2} The limit comes directly.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...